2005
DOI: 10.1097/01.pec.0000186424.84764.94
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergencies on a US-Based Commercial Airline

Abstract: The most common in-flight pediatric emergencies involved infectious diseases and neurological and respiratory tract problems. Emergency medical kits should be expanded to include pediatric medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
3
28
3
2
Order By: Relevance
“…One study of an 8-year period for a single US commercial airline reported 169 paediatric emergencies of which 22 were respiratory 55. The presence of pre-existing lung disease in these children was not reported.…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…One study of an 8-year period for a single US commercial airline reported 169 paediatric emergencies of which 22 were respiratory 55. The presence of pre-existing lung disease in these children was not reported.…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…The quality of data from studies reporting reactions on airplanes is poor also due to reluctance in survey response (75); however, the data suggest that a small number of reactions occur in this context, some of which are severe. Airline companies show inconsistency, for example, regarding provision of peanuts on board aircraft and requests for special assistance (76)(77)(78)(79)(80). Allergic reactions constituted only 2.2% of medical emergencies during commercial passenger flights in the USA (81).…”
Section: Providers Of Non-prepacked Foodsmentioning
confidence: 99%
“…The majority of pediatric in-flight emergencies are related to infections (fever and otitis media), neurological conditions (syncope and seizures), and respiratory issues (asthma exacerbations) (7). These emergencies tend to be self-limited, seldom require alteration of the planned flight route, and do not pose a significant risk to life (7).…”
mentioning
confidence: 99%
“…When a medical emergency arises during flight, care is provided by crewmembers and volunteers with a medical background and increasingly more often in consultation with a specialized ground-based medical support (GBMS) center (3)(4)(5)(6)(7). The majority of pediatric in-flight emergencies are related to infections (fever and otitis media), neurological conditions (syncope and seizures), and respiratory issues (asthma exacerbations) (7). These emergencies tend to be self-limited, seldom require alteration of the planned flight route, and do not pose a significant risk to life (7).…”
mentioning
confidence: 99%